OSS (Outer Solar System): a fundamental and planetary physics mission to Neptune, Triton and the Kuiper Belt - Christophe, Bruno; Postberg, Frank (Experimental astronomy, 2012)
The present OSS (Outer Solar System) mission continues a long and bright tradition by associating the communities of fundamental physics and planetary sciences in a single mission with ambitious goals in both domains. OSS is an M-class mission to explore the Neptune system almost half a century after the flyby of the Voyager 2 spacecraft. Several discoveries were made by Voyager 2, including the Great Dark Spot (which has now disappeared) and Triton’s geysers. Voyager 2 revealed the dynamics of Neptune’s atmosphere and found four rings and evidence of ring arcs above Neptune. Benefiting from a greatly improved instrumentation, a mission as OSS would result in a striking advance in the study of the farthest planet of the solar system. Furthermore, OSS would provide a unique opportunity to visit a selected Kuiper Belt object subsequent to the passage of the Neptunian system. OSS would help consolidate the hypothesis of the origin of Triton as a Kuiper Belt object captured by Neptune, and to improve our knowledge on the formation of the solar system. The OSS probe would carry instruments allowing precise tracking of the spacecraft during the cruise. It would facilitate the best possible tests of the laws of gravity in deep space. These objectives are important for fundamental physics, as they test General Relativity, our current theoretical description of gravitation, but also for cosmology, astrophysics and planetary science, as General Relativity is used as a tool in all these domains. In particular, the models of solar system formation uses General Relativity to describe the crucial role of gravity. OSS is proposed as an international cooperation between ESA and NASA, giving the capability for ESA to launch an M-class mission towards the farthest planet of the solar system, and to a Kuiper Belt object. The proposed mission profile would allow to deliver a 500 kg class spacecraft. The design of the probe is mainly constrained by the deep space gravity test in order to minimize the perturbation of the accelerometer measurement.
Gesehen am 19.07.2018